Effects of robot assisted gait training in progressive supranuclear palsy (PSP): a preliminary report - Sale, Patrizio; Stocchi, Fabrizio; Galafate, Daniele; De Pandis, Maria Francesca; Le Pera, Domenica; Sova, Ivan; Galli, Manuela; Foti, Calogero; Franceschini, Marco (Frontiers in Human Neuroscience, 2014)
Background and Purpose: Progressive supranuclear palsy (PSP) is a rare neurodegenerative disease clinically characterized by prominent axial extrapyramidal motor symptoms with frequent falls. Over the last years the introduction of robotic technologies to recover lower limb function has been greatly employed in the rehabilitative practice. This observational trial is aimed at investigating the feasibility, the effectiveness and the efficacy of end-effector robot training in people with PSP. Method: Pilot observational trial. Participants: Five cognitively intact participants with PSP and gait disorders. Interventions: Patients were submitted to a rehabilitative program of robot-assisted walking sessions for 45 minutes, 5 times a week for 4 weeks. Main outcome measures: The spatiotemporal parameters at the beginning (T0) and at the end of treatment (T1) were recorded by a gait analysis laboratory. Results: Robot training was feasible, acceptable and safe and all participants completed the prescribed training sessions. All patients showed an improvement in the gait index (Mean velocity, Cadence, Step length and Step width) (T0 versus T1). Conclusions: Robot training is a feasible and safe form of rehabilitation for cognitively intact people with PSP. This innovative approach can contribute to improve lower limb motor recovery. The focus on gait recovery is another quality that makes this research important for clinical practice. On the whole, the simplicity of treatment, the lack of side effects and the positive results in the patients support the recommendation to extend the trials of this treatment. Further investigation regarding the effectiveness of robot training in time is necessary. Trial registration: ClinicalTrials.gov NCT01668407.